2019
DOI: 10.12782/specdiv.24.217
|View full text |Cite
|
Sign up to set email alerts
|

Two New Species of <i>Microloxoconcha</i> (Crustacea: Ostracoda) from the Sublittoral Zone in Western Japan

Abstract: In the present study, we describe two new marine species, Microloxoconcha toyoshioae n. sp. and M. sublittoralis n. sp., collected from the sandy bottom in the western part of Japan, from the depths of approximately 20 to 30 m and 50 m, respectively. This represents the first record of this genus from such depths, since all 10 previously described species are known from the beach interstitial waters. We suspect the two new species are most probably also inhabiting spaces between sand grains since they have ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Other studies have reported their presence in the supralittoral zone (Hiruta et al 2007) and in estuaries, which are a part of the intertidal zone . Additionally, they can be found at a depth of more than 10 m from the sea floor (Tanaka & Ohtsuka 2019;Tanaka et al 2020). However, since these species were collected from relatively deep water using samplers, it is unclear whether they are strictly interstitial species.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported their presence in the supralittoral zone (Hiruta et al 2007) and in estuaries, which are a part of the intertidal zone . Additionally, they can be found at a depth of more than 10 m from the sea floor (Tanaka & Ohtsuka 2019;Tanaka et al 2020). However, since these species were collected from relatively deep water using samplers, it is unclear whether they are strictly interstitial species.…”
Section: Introductionmentioning
confidence: 99%